KINERJA APARATUR DINAS PERDAGANGAN KOPERASI DAN USAHA KECIL MENENGAH DALAM PELESTARIAN TENUN IKAT DI KABUPATEN SIKKA PROVINSI NUSA TENGGARA TIMUR - Sina, Irmgard Y. N.; Tefa, Gradiana (Jurnal MSDA (Manajemen Sumber Daya Aparatur), 2019)
The tie Weaving of Sikka is a cultural heritage that currently it’s preservation is not really famous among woman in Sikka Regency, East Nusa Tenggara. This research aims to determine the performance of the apparatus Department of Trade Cooperatives and Small and Medium Enterprises (SMEs) in elevate people awareness to preserve the tie weaving of Sikka, also to know the inhibiting factors and efforts already made by the department. The method used is descriptive research method with inductive approach. Data collection techniques used were observation, interviews and documentation The results shows that in the field is the preservation already running, but there are still some inhibiting factors. Besides the efforts of the government, the weavers must have an active participation in this preservation process so as to achieve the purpose of the process is to be achieved.